How to write paper in journals - Said, Ismail (Jurnal Alam Bina, 2007)
Journal paper is a scholarly document, a sound judgment of a scholar on a particular subject matter. It is a concise, clear and accurate report; discussing a problem and its solution achieved through rigorous, valid methodology. It is not an aggregate of anecdotal evidences gathered by a researcher. Scientific publishing is a rigorous effort of writing facts derived from a valid methodology. The information is accurate and current: relevant to the discipline of knowledge. Inasmuch, publishing is an act of disseminating of the knowledge to peers. Scholarly journals are actively involved in the creation and diffusion of knowledge. The function of a journal is a function of how useful it is a source of knowledge.